Comparative and international education (re)assembled examining a scholarly field through an assemblage theory lens - Salajan, Florin; Jules, Tavis Deryck 1980- (Bloomsbury Academic, 2022)
"Drawing on a post-foundational approach to Deleuze and Guattari's seminal work on assemblage theory, this book explores the scholarly field of comparative and international education (CIE). Written by a diverse collection of international scholars from Georgia, Ireland, Italy, Malaysia, South Africa, Sweden, Switzerland, the UK and the USA, the chapters use the assemblage paradigm as an analytical tool to examine the continuously evolving field of CIE. The theoretical chapters unpack assemblage theory and its core components, whilst others draw on examples and international case studies to show how assemblage theory could be applied to future CIE research. The field of CIE is prone to constant (re)configurations and this book casts the shaping of the field in a fresh light, prompting new discussions on the field's variability and flexibility."
Keywords: Comparative education; International education; System theory / Social aspects; Poststructuralism